Wolves contribute to disease control in a multi-host system. Scientific reports. - Tanner, Eleanor; White, A.; Acevedo Lavandera, Pelayo; Balseiro, Ana; Marcos, J; Gortázar, Christian (Scientific Reports, 2019)
We combine model results with field data for a system of wolves (Canis lupus) that prey on wild boar (Sus scrofa), a wildlife reservoir of tuberculosis, to examine how predation may contribute to disease control in multi-host systems. Results show that predation can lead to a marked reduction in the prevalence of infection without leading to a reduction in host population density since mortality due to predation can be compensated by a reduction in disease induced mortality. A key finding therefore is that a population that harbours a virulent infection can be regulated at a similar density by disease at high prevalence or by predation at low prevalence. Predators may therefore provide a key ecosystem service which should be recognised when considering human-carnivore conflicts and the conservation and re-establishment of carnivore populations.